Analysis of surface errors and subsurface damage in flexible grinding of optical fused silica. Issue 1 (January 2017) - Lin, X.; Zhang, J.; Tang, H.; Du, X.; Guo, Y.
Abstract The surface errors and subsurface damage (SSD) formed during optical fused silica grinding processes have been investigated using the flexible grinding wheel (FGW). Surface errors, including low spatial frequency (LSF) errors, middle spatial frequency (MSF) errors, and high spatial frequency (HSF) errors, and SSD depths are measured. Compared with the rigid grinding wheel (RGW), it is found that the influences of grinding parameters on surface errors and SSD are the same in flexible grinding. However, LSF and HSF errors and SSD depths are obviously decreased and MSF errors are partly controlled. The grinding surface micrographs are also observed, and the surfaces after flexible grinding have less grinding scratches and surface defects. These results indicate that flexible grinding using FGW has high precision and elastic characteristics and can achieve good surface quality of optical fused silica.